2012
DOI: 10.1002/bmc.2772
|View full text |Cite
|
Sign up to set email alerts
|

Liquid chromatography and mass spectrometry of haem biosynthetic intermediates: a review

Abstract: This article discusses the separation, analysis and characterisation of intermediates and oxidative by-products of the haem biosynthetic pathway by liquid chromatography and mass spectrometry. Techniques reviewed include high-performance liquid chromatography, ultra-high-performance liquid chromatography, capillary electrophoresis, ion mobility spectrometry, mass spectrometry and tandem mass spectrometry. The emphasis was on the analysis of biological and clinical samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 159 publications
0
8
0
Order By: Relevance
“…Although ALA and PBG can be monitored in both positive and negative ionization modes (Benton and Lim, ; Benton et al ., ), positive ionization mode was used for this study as it offered increased sensitivity. The protonated [M + H] + PBG ion ( m/z 227) showed significant loss of NH 3 in the ion source ([M + H − NH 3 ] + ) to give a stable, positively charged methylenepyrrolenine ion ( m/z 210; Lord et al ., ; Benton et al ., 2012a, 2012b), as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although ALA and PBG can be monitored in both positive and negative ionization modes (Benton and Lim, ; Benton et al ., ), positive ionization mode was used for this study as it offered increased sensitivity. The protonated [M + H] + PBG ion ( m/z 227) showed significant loss of NH 3 in the ion source ([M + H − NH 3 ] + ) to give a stable, positively charged methylenepyrrolenine ion ( m/z 210; Lord et al ., ; Benton et al ., 2012a, 2012b), as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Eluent A was 10% acetonitrile (v/v) in 1 mol/l aqueous ammonium acetate – acetic acid buffer, pH 5.16 and eluent B was 10% acetonitrile in methanol. Previous studies have shown that a high molar concentration of ammonium acetate buffer (1 mol/l, pH 5.16) is essential for the separation of type I and III uroporphyrin and heptacarboxylic acid porphyrin isomers. Lower molar concentrations tend to give peak broadening with the consequent loss of chromatographic resolution.…”
Section: Methodsmentioning
confidence: 99%
“…We have developed LC‐MS and LC‐MS/MS systems for the rapid separation and characterisation of porphyrins in biological materials . Here we report the further separation and characterisation of hydroxyisocoproporphyrin, ketoisocoproporphyrin, deethylisocoproporphyrin and isocoproporphyrin using UHPLC‐ESI‐exact mass MS/MS, which will greatly assist in the structural elucidation of isocoproporphyrin and its derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…While ALA and PBG, the early precursors of heme synthesis pathway, increase during the acute episodes, the increase in porphyrins, i.e. the late substrates, becomes more significant in the chronic period [3].…”
Section: Introductionmentioning
confidence: 99%